Physiological signals based human emotion recognition: A review - S., Jerritta; M., Murugappan; Ramachandran, Nagarajan, Prof. Dr.; Wan Khairunizam, Wan Ahmad, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/